Agreement between anatomical M‐mode and tissue Doppler imaging in the assessment of fetal atrioventricular annular plane displacement in uncomplicated pregnancies: A prospective longitudinal study. Issue 11 (23rd August 2019) - Zanardini, Cristina; D'Antonio, Francesco; Hvingel, Bodil; Vårtun, Åse; Prefumo, Federico; Flacco, Maria E.; Manzoli, Lamberto; Acharya, Ganesh
Abstract: Aim: To evaluate the level of agreement between M‐mode and pulsed‐wave tissue Doppler imaging (PW‐TDI) techniques in assessing fetal mitral annular plane systolic excursion (MAPSE), tricuspid annular plane systolic excursion (TAPSE) and septal annular plane systolic excursion (SAPSE) in a low‐risk population. Methods: This prospective longitudinal study included healthy fetuses assessed from 18 to 40 weeks of gestation. Tricuspid annular plane systolic excursion, MAPSE and SAPSE were measured using anatomical M‐mode and PW‐TDI. The agreement between the two diagnostic tests was assessed using Bland–Altman analysis. Results: Fifty fetuses were included in the final analysis. Mean values of TASPE were higher than that of MAPSE. There was a progressive increase of TAPSE, MAPSE and SAPSE values with advancing gestation. For each parameter assessed, there was an overall good agreement between the measurements obtained with M‐mode and PW‐TDI techniques. However, the measurements made with M‐mode were slightly higher than those obtained with PW‐TDI (mean differences: 0.03, 0.05 and 0.03 cm for TAPSE, MAPSE and SAPSE, respectively). When stratifying the analyses by gestational age, the mean values of TAPSE, MAPSE and SAPSE measured with M‐Mode were higher compared to those obtained with PW‐TDI, although the mean differences between the two techniques tended to narrow with increasing gestation. Tricuspid annular plane systolic excursion, MAPSE and SAPSE measurements were all significantly, positively associated with gestational age (all P < 0.001). Conclusion: Fetal atrioventricular annular plane displacement can be assessed with M‐mode technique, or with PW‐TDI as the velocity‐time integral of the myocardial systolic waveform. Atrioventricular annular plane displacement values obtained with M‐mode technique are slightly higher than those obtained with PW‐TDI.